Investigation Process in Criminal Suspection Children on Theft by Weighting in SatReskrim Polrestabes Semarang - Adimas Dirgantara (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
The problem in this research are: the investigation process child suspects in criminal offenses of theft by weighting on Sat Reskrim Polrestabes Semarang, factors inhibiting the investigation of criminal theft by weighting with child actors in Semarang and Sat Reskrim Polrestabes solutions to obstacles investigation of criminal offenses of theft by weighting with child actors in Sat Reskrim Polrestabes Semarang. The methodology used by researchers is juridical empirical approach. While sources and types of data in this study are primary data obtained from field studies with interviews with investigators on Sat Reskrim Polrestabes Semarang. And secondary data obtained from the study of literature. Based on the results of studies that (1) the investigation process child suspects in criminal offenses of theft by weighting, while the act of investigation are as follows: Receiving Reports, Take First Action, arrest and detention, confiscation, examination of the suspect and witness, Termination of Investigation, completion of the investigation. (2) obstacles encountered by investigators in investigating the crime of theft by weighting with the perpetrator of children in Polrestabes Semarang certainly be affected by several factors that can facilitate or complicate and greatly affect the performance of members of the investigator to conduct an investigation (3) obstacles that arise in investigation in this case Polrestabes Semarang making efforts to overcome these barriers. Keywords: Investigation Process; The Child Actors; Crime; Theft By Weighting.